2023
DOI: 10.3389/fnagi.2023.1209385
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German Montreal-Cognitive-Assessment-H for hearing-impaired

Abstract: BackgroundHearing loss and dementia are highly prevalent in older age and often co-occur. Most neurocognitive screening tests are auditory-based, and performance can be affected by hearing loss. To address the need for a cognitive screening test suitable for people with hearing loss, a visual version of the Montreal-Cognitive-Assessment was developed and recently validated in English (MoCA-H), with good sensitivity and specificity for identifying cases of dementia. As the MoCA is known to perform differently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Adapted versions of the MMSE and MoCA to account for hearing loss were administered in 14 and seven studies, respectively. Furthermore, in two studies published post-search, there are now validated English 18 and German 19 versions of the MOCA-H for adults with hearing impairment. Due to the wide-range of global cognitive function tests used, tests that were used in only a single study pre- or post-2017 were categorized as “other” with corresponding references provided (eg, Blessed Information-Memory Concentration Test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted versions of the MMSE and MoCA to account for hearing loss were administered in 14 and seven studies, respectively. Furthermore, in two studies published post-search, there are now validated English 18 and German 19 versions of the MOCA-H for adults with hearing impairment. Due to the wide-range of global cognitive function tests used, tests that were used in only a single study pre- or post-2017 were categorized as “other” with corresponding references provided (eg, Blessed Information-Memory Concentration Test).…”
Section: Resultsmentioning
confidence: 99%
“… 12 However, sensory deficits (eg, hearing loss) have the potential to impact adversely on cognitive test performance, leading to a subsequent overestimation of cognitive decline. 13 , 14 Adapted versions of cognitive assessment tools have therefore been developed to address this impact (eg, written-MMSE; 15 , 16 MoCA-Hearing-Impaired, 17 and more recently, a validated version (MOCA-H) in English 18 and in German; 19 Cambridge Neuropsychological Test Automated Battery (CANTAB), 20 Repeated Battery for the Assessment of Neuropsychological Status for Hearing Impaired Individuals (RBANS-H)). 21 Other computerised test batteries that can be used for assessment of cognitive impairment are the RBANS, Cogstate, 22 ALACog, 23 the CDR computerized assessment system (CDR system), 24 and Factors of Longitudinal Attention, Memory and Executive Function (FLAME) test batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The younger groups were students from these universities, and the older groups were recruited from the respective communities. Older participants were screened for mild cognitive impairment through the Montreal Cognitive Assessment questionnaire (MoCA, Nasreddine et al, 2005), and all achieved a score >= 23 (Table 1), the cut-off point recommended by Carson et al (2018;Völter et al, 2023;see Engedal et al, 2022, for normative data for Norwegian older adults). All participants had normal or corrected-to-normal vision and gave written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…The study also found that individuals with normal sensory acuity performed better in the MoCA than those with sensory loss, despite modifying the scores of the MoCA test for people with sensory loss. These findings led to the development of a version of the MoCA for people with hearing loss (MoCA-H) (Dawes et al, 2023;Völter et al, 2023).…”
Section: Introductionmentioning
confidence: 99%